2020
DOI: 10.3390/app10051622
|View full text |Cite
|
Sign up to set email alerts
|

Double Deep Q-Network with a Dual-Agent for Traffic Signal Control

Abstract: Adaptive traffic signal control (ATSC) based on deep reinforcement learning (DRL) has shown promising prospects to reduce traffic congestion. Most existing methods keeping traffic signal phases fixed adopt two agent actions to match a four-phase suffering unstable performance and undesirable operation in a four-phase signalized intersection. In this paper, a Double Deep Q-Network (DDQN) with a dual-agent algorithm is proposed to obtain a stable traffic signal control policy. Specifically, two agents are denote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The comparison was performed based on the simulation model and the obtained results indicate the superiority of the algorithm as compared to a fixed time and the longest queue first algorithm. In [25] the four-phase isolated intersection adaptive traffic signal control based on the double DQN (DDQN) is proposed. Fixed phase sequence stable traffic signal control policy is achieved using dual agent architecture.…”
Section: The Related Workmentioning
confidence: 99%
“…The comparison was performed based on the simulation model and the obtained results indicate the superiority of the algorithm as compared to a fixed time and the longest queue first algorithm. In [25] the four-phase isolated intersection adaptive traffic signal control based on the double DQN (DDQN) is proposed. Fixed phase sequence stable traffic signal control policy is achieved using dual agent architecture.…”
Section: The Related Workmentioning
confidence: 99%
“…In [27], the authors proposed using a knowledge exchange protocol between agents to increase the level of cooperation between agents and achieve an optimal traffic light control strategy. A double Q-learning algorithm for improving the stability of control policy was investigated in [28]. In [29], the authors combined the recurrent neural network (RNN) with Deep Q-Network and showed that the proposed approach performs better in partially observed environment.…”
Section: Related Workmentioning
confidence: 99%
“…The route of each car is generated by the path generator randomly. The method by which vehicles are generated and departed into the network significantly impacts any traffic simulation quality [26]. The most popular vehicle production method is to randomly sample from probability distribution numbers that respect to the time interval between vehicles.…”
Section: A Experimental Settingsmentioning
confidence: 99%